1977
DOI: 10.1111/j.2042-7158.1977.tb11330.x
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacology of benoxaprofen (2-[4-chlorophenyl]-α-methyl-5-benzoxazole acetic acid), LRCL 3794, a new compound with anti-inflammatory activity apparently unrelated to inhibition of prostaglandin synthesis

Abstract: Benoxaprofen is a potent and long‐acting anti‐inflammatory and antipyretic compound. Its anti‐inflammatory activity has been demonstrated in carrageenan‐induced oedema, in cellulose pellet granuloma and in both developing and established adjuvant arthritis tests in rats. Its antipyretic activity is greater than either aspirin or paracetamol in tests inducing pyrexia with yeast or ‘E’ pyrogen in rats and rabbits. Benoxaprofen has analgesic activity in tests where pain is accompanied by inflammation but not in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
46
0

Year Published

1977
1977
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(46 citation statements)
references
References 14 publications
0
46
0
Order By: Relevance
“…The present study was designed to examine the efficacy of six agents that have been shown to inhibit leukotriene synthesis in leukocytes and, in some cases, lung tissue and to inhibit the contraction of the airways induced by antigen and calcium ionophore A23 187. The compounds include nafazatrom (Mardin & Busse, 1983), 3-amino-i-[m-trifluoromethyl)-phenyl]-2-pyrazoline (BW755C) (Higgs et al, 1979), nordihydroguaiaretic acid (NDGA) (Tappel et al, 1953), benoxaprofen (Cashin et al, 1977), 6,9-deoxy-6,9-Nphenylimino-A6,8 prostaglandin b1 (piriprost) (Bach et al, 1982) and diethylcarbamazine citrate (DECC) (Harned et al, 1948). In addition sodium 7-[3-(4-acetyl -3-hydroxy-2-propylphenoxy)-2-hydroxypropoxy]-4-oxo-8-propyl-4H-benzopyran-2-carboxylate (FPL55712) (Augstein et al, 1973) was examined as it blocks peptidoleukotriene receptors in the airways (Sheard et al, 1977;Jones et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…The present study was designed to examine the efficacy of six agents that have been shown to inhibit leukotriene synthesis in leukocytes and, in some cases, lung tissue and to inhibit the contraction of the airways induced by antigen and calcium ionophore A23 187. The compounds include nafazatrom (Mardin & Busse, 1983), 3-amino-i-[m-trifluoromethyl)-phenyl]-2-pyrazoline (BW755C) (Higgs et al, 1979), nordihydroguaiaretic acid (NDGA) (Tappel et al, 1953), benoxaprofen (Cashin et al, 1977), 6,9-deoxy-6,9-Nphenylimino-A6,8 prostaglandin b1 (piriprost) (Bach et al, 1982) and diethylcarbamazine citrate (DECC) (Harned et al, 1948). In addition sodium 7-[3-(4-acetyl -3-hydroxy-2-propylphenoxy)-2-hydroxypropoxy]-4-oxo-8-propyl-4H-benzopyran-2-carboxylate (FPL55712) (Augstein et al, 1973) was examined as it blocks peptidoleukotriene receptors in the airways (Sheard et al, 1977;Jones et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Benoxaprofen ( Figure 1) is a novel acidic compound (Dunwell, Evans, Hicks, Cashin & Kitchen, 1975) exhibiting notable anti-inflammatory, analgesic and antipyretic activity in animals (Cashin, Dawson & Kitchen, 1977). Single-dose studies in several animal species have shown that the compound is well absorbed after oral administration .…”
Section: Introduction Methodsmentioning
confidence: 99%
“…2 These are used to cure cold, fever and inflammation in various musculoskeletal disorders, menstrual cramps, and body pains. [3][4][5][6][7][8][9] The conventional synthesis of these drugs reported in the literature, 10,11 has certain drawbacks such as the formation of hazardous chemicals like cyanides, and low yields due to high temperatures required, which make these methods inefficient. In this paper, we report the synthesis using an electrochemical approach.…”
Section: Introductionmentioning
confidence: 99%